Dementia Worry and Neuropsychological Performance in Healthy Older Adults - Caughie, Cali; Bean, Phoebe; Tiede, Paul; Cobb, Joshua; McFarland, Craig; Hall, Stuart (Archives of clinical neuropsychology, 2021)
Dementia is one of the most feared diseases in American society. However, limited research exists regarding how worrying about dementia may influence peoples' cognitive abilities. The current study examines how dementia worry affects performance on neuropsychological domains of executive function, memory, attention, and processing speed in a healthy older adult population. Participants (n = 40) were screened for depression using the Patient Health Questionnaire-8 (PHQ-8, scores > 10 were excluded) and for mild cognitive impairment using the Telephone Interview for Cognitive Status (TICS, scores < 32 were excluded). All participants were administered common neuropsychological tests of executive function, memory, attention, and processing speed. Participants were also asked to complete the Dementia Worry Scale (DWS), a measure assessing the level of dementia worry individuals experience in daily life. A multivariate effect of dementia worry on neuropsychological measures of executive function was supported. Specifically, higher levels of dementia worry were significantly related to poorer performance on combined measures of executive function (Wilk's Lambda = 0.821, F (2, 36) = 3.934, p = .028). Dementia worry significantly affects scores on specific neuropsychological measures. Inasmuch, dementia worry may have both functional implications for older adults, as well as assessment implications for practicing neuropsychologists. Further research is necessary to parse apart whether dementia worry represents a psychological variable affecting cognitive performance and/or serves as an early marker of cognitive decline.